2018
DOI: 10.1016/j.theriogenology.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy diagnosis in cattle using pregnancy associated glycoprotein concentration in circulation at day 24 of gestation

Abstract: Cattle producers are limited to day 28-30 of gestation as the earliest time point for accurate pregnancy diagnosis due to the effectiveness of ultrasound and chemical based methods, including commercially available pregnancy associated glycoproteins (PAG) tests. The objective of the current studies were to determine if early gestation circulating PAG concentrations at day 24 could be used to diagnose pregnancy in dairy cattle undergoing embryo transfer. In vitro produced embryos were transferred into Holstein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 43 publications
(64 reference statements)
0
28
0
Order By: Relevance
“…In addition to the high rate of false positives, false negative diagnosis can be an issue as circulating PAG concentrations increase at different rates in individual cows. Reese et al (2018) reported up to a 55% false negative rate using a 90% confidence cutoff value; whereas, Middleton and Pursley (2019), using a different antibody-assay combination, observed a 6% false negative rate indicating that antibody selection towards early secreted PAGs is critical. One challenge is day 24 PAG concentrations exhibit increased variability compared to day 30 samples, making it more difficult to establish cutoff values for pregnancy success or embryonic mortality predictions.…”
Section: Chemical-based Methods: Pregnancy Specific Pregnancy Associamentioning
confidence: 97%
“…In addition to the high rate of false positives, false negative diagnosis can be an issue as circulating PAG concentrations increase at different rates in individual cows. Reese et al (2018) reported up to a 55% false negative rate using a 90% confidence cutoff value; whereas, Middleton and Pursley (2019), using a different antibody-assay combination, observed a 6% false negative rate indicating that antibody selection towards early secreted PAGs is critical. One challenge is day 24 PAG concentrations exhibit increased variability compared to day 30 samples, making it more difficult to establish cutoff values for pregnancy success or embryonic mortality predictions.…”
Section: Chemical-based Methods: Pregnancy Specific Pregnancy Associamentioning
confidence: 97%
“…Two plasma controls containing moderate (2.0 ng/mL) and low (1.0 ng/mL) PAG concentrations were included in each plate. Plasma concentrations of PAG were also measured by a monoclonal-based PAG in-house ELISA (in-house) as described by Green et al (2005) and modified by Pohler et al (2016) and Reese et al (2018), as well as a second commercial assay (A2; Idexx, Westbrook, ME). The in-house assay uses a polyclonal antibody raised against first-secreted PAG (Ab 63; Reese et al, 2018), whereas the antigen used to create a detection antibody for A2 consisted of a mixture of PAG (PAG 4,6,9,16,18,and 19;US Patent no.…”
Section: Circulating Pag Concentrationsmentioning
confidence: 99%
“…on recipient plasma concentrations of pregnancy-associated glycoproteins (PAG). Blood samples were collected weekly from days 28 to 91 of gestation and plasma concentrations of PAG were measured using two commercial PAG ELISA antibody combinations (A1 [Panel A] and A2 [Panel B]), and an in-house monoclonal-based PAG 63 ELISA (Panel C) as described by Green et al (2005) and modified by Reese et al (2018). A1: embryo breed × day (P < 0.01).…”
mentioning
confidence: 99%
“…PAG can be measured in maternal blood circulation (Shahin et al, 2013). Pregnancy is diagnosed using PAG test on day 24 of gestation (Reese et al, 2017). The knowledge of mechanisms involved in the production and control of PAG is beneficial in livestock breeding and facilitates diagnosis of pregnancy (Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%